The Relationship of Gravida, Gestational Age, and Education with Gingivitis and Periodontitis in Pregnant Women with Malocclusion - Muntadir, Lila; Rinata, Evi; Ashari, Tontowi; Setyawardana, Eka; Puspitasari, Dini Ayu; Tsabita, Nabila Fatya (Cakradonya Dental Journal, 2025)
Hormonal changes, number of pregnancies (gravida), gestational age, education level, and the presence of malocclusionespecially if accompanied by the use of bracescan increase the risk of gingivitis and periodontitis in pregnant women. This study aims to analyze the relationship between gravida, gestational age, and education level on the incidence of gingivitis in pregnant women with malocclusion. The study involved 51 pregnant women who met the inclusion criteria and provided consent by signing an informed consent form. Interviews and oral screenings were conducted, and the data were analyzed using the Chi-squared test. The results of this study found that the number of pregnancies (gravida) had a significant relationship with the incidence of gingivitis (p = 0.024) and dental caries (p = 0.029). Gestational age showed a significant relationship with the incidence of periodontitis (p = 0.003) and dental caries (p = 0.020). Meanwhile, educational level did not show a significant relationship with gingivitis or periodontitis, but was significantly associated with dental caries (p = 0.050). It is concluded that there is a significant relationship between gravida, gestational and education level with dental caries in pregnant women with malocclusion. Gestational age is significantly associated with periodontitis, and gravida is significantly associated with gingivitis.